Keanekaragaman Plankton di Danau Ceramin Bekas Tambang Intan Banjarbaru - Elda Juwiyatri; Anjar Pribadi; Rizqi Fithratullah (Syntax Literate, 2023)
South Kalimantan has the potential to develop tourism, one of the place is ex mined diamond in Banjarbaru. The aspects that need to consider in the management and development of tourism are the aspect of cleanliness and safety in freshwater. One of microorganism can determine life in water is plankton. The study determined the community structure of plankton found at ceramin lake ex mined diamond lake Banjarbaru. Sampling was taken from Ceramin lake with different depths of 0 meters, 3 meters, and 6 meters. Sample of each depth was taken 4 times. Result showed in Ceramin lake consist of 4 phyla for Fitoplankton, Euglenophyta (1 spesies), Chlorophyta (2 spesies), Cyanobacteria (1 spesies), Bacilarophyta (3 spesies), dan Zooplankton yang ditemukan terdiri 1 filum yaitu Rotifera (2 spesies).